Optimization of steel reinforcement in reinforced concrete beam with openings by numerical and experimental comparison / Mohd Najmi Bahrudin - Bahrudin, Mohd Najmi (2006)
The purposed of the study is to optimize the reinforcement in RC beam that have transverse openings at the web section of the beam. The laboratory works results (actual results) are compared with the results using simulation in order to determine the behavior of the reinforced concrete beam. The comparison process is one of the important processes in this research in order to fully utilize the simulation works in the future.The behaviors of the RC beam in terms of cracking pattern, ultimate strength, mode of failure and also the deformation are obtained from experimental works and simulation using LUSAS software. All the experimental works are carried out at the Heavy Structure Laboratory of UiTM Pulau Pinang.The comparison shows that the results obtained from experimental works and simulation using LUSAS software are quiet close to each other. The simulation works shows that it can be use to investigate the behaviors of the actual beam in order to understand the reason behind the results that obtained from experimental works.